Pengaruh Pelatihan Dan Kemampuan Kerja Terhadap Kinerja Karyawan Pada PT Jakarta Baru Cosmopolitan Di Gading Serpong - Nur Annisa Salsabilla; Nariah Nariah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Training and Work Ability on the Performance of Employees at Jakarta Baru Cosmopolitan. The method used in this research is a descriptive method with a quantitative approach. The population in this study is all employees of PT Jakarta Baru Cosmopolitan, and the sample in this study uses the simple random sampling technique with a 5% margin of error. The data analysis technique is simple and multiple linear regression. The research results indicate that partially, Training (X1) has a positive effect on Employee Performance (Y) with a regression value of Y = 6.640 + 1.300X1 and a coefficient of determination of 72.2% and t-count of 15.044 > 1.988. Therefore, it can be concluded that H1 is accepted and Ha is rejected. Work Ability (X2) has a positive effect on Employee Performance (Y) with a regression value of Y = 67.814 – 0.517X2 and a coefficient of determination of 8.3%, supported by t-count 2.812 > 1.988. Therefore, H2 is accepted and Ha is rejected. Training and Work Ability simultaneously have a regression value of Y = 12.485 + 1.269X1 – 0.149X2 and a coefficient of determination of 72.9% and an F-count of 115.574 > 2.71. Therefore, H3 is accepted and Ha is rejected.